Commentary on Harper S, Strumpf EC, Kaufman JS. Do Medical Marijuana Laws Increase Marijuana Use? Replication Study and Extension - Wall, Melanie M. (2012)
Replicability is a crucial element of good science, particularly so when the subject matter is sensitive and political. Therefore, we welcome close scrutiny of our brief report in the Annals of Epidemiology in 2011, “Adolescent Marijuana Use from 2002 to 2008: Higher in States with Medical Marijuana Laws, Cause Still Unclear.” We were glad to see that Harper et al. (1) were able to replicate our results showing that states with medical marijuana laws (MML) showed greater rates of marijuana use among their residents during 2002 to 2008 and that states that passed MML after 2002 already had greater use among their residents before they passed the law. However, we have several concerns with the additional analyses run by Harper et al. and further concerns with the way their results were presented. We summarize our concerns in this commentary.